2014
DOI: 10.1159/000365214
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis and Patient Preferences in Patients with Neural Tube Defects around the Advent of Fetal Surgery in Belgium and Holland

Abstract: Introduction: We review the characteristics and prenatal choices of patients recently evaluated for neural tube defects (NTD) at two tertiary units. The prenatal diagnosis of NTD allows parents to consider all prenatal options. In selected cases of spina bifida aperta this also includes fetal surgery, which we started offering after combined ‘in-house' and ‘exported' training. Material and Methods: This is a retrospective review of prospectively collected data on NTD diagnosed over the last 8 years and recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
0
32
2
6
Order By: Relevance
“…Actual uptake of fMMC surgery amongst eligible cases was 18% when it required a cross‐border referral but increased to 75% when the intervention became available locally. The latter number is much higher than that reported by Ovaere et al and by Mazzone et al in two European cohort studies, where only six of 14 (42.8%) eligible patients and 56 of 106 (53%) eligible patients, respectively, underwent the intervention. It is also higher than the numbers reported by Moldenhauer et al in the United States after the MOMS trial, where only 29% of those eligible for surgery underwent the procedure.…”
Section: Discussioncontrasting
confidence: 54%
“…Actual uptake of fMMC surgery amongst eligible cases was 18% when it required a cross‐border referral but increased to 75% when the intervention became available locally. The latter number is much higher than that reported by Ovaere et al and by Mazzone et al in two European cohort studies, where only six of 14 (42.8%) eligible patients and 56 of 106 (53%) eligible patients, respectively, underwent the intervention. It is also higher than the numbers reported by Moldenhauer et al in the United States after the MOMS trial, where only 29% of those eligible for surgery underwent the procedure.…”
Section: Discussioncontrasting
confidence: 54%
“…A European center recently reported that 76% of prenatal diagnoses of spina bifida resulted in termination, and the authors found that requests were not correlated with the severity of disease [32] . The results of the MOMS trial may modify this number as perceptions surrounding open maternal-fetal surgery change.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the cultural characteristics of Brazilian women, who are more tolerant of open surgeries such as cesarean sections, allow the performance of a higher number of open surgeries for intrauterine MMC repair. These cultural characteristics are different from those of European women [21]. …”
Section: Discussionmentioning
confidence: 99%